KELAYAKAN USAHA MINYAK KELAPA DI DESA LOMBONG TIMUR, KECAMATAN MALUNDA, SULAWESI BARAT - Indrayana, Ketut; Kusrini, Nini; Ricky, Muhammad (LPPM Universitas Muhammadiyah Mamuju, 2020)
ABSTRACT The Appropriateness Of Coconut Oil Business In East Lombong Village, Of Malunda West Sulawesi Coconut oil comes from agricultural product. East Lombong village, Kec. Malunda, Kab. Majene is one the villages that has a lot of agribusiness activities, as like coconut oil business in household scale, and one of the manufacturers is Mrs. Rubiah. This research aims to analyze the feasibility of the business. The research was conducted in East Lombong village, Kec. Malunda, Kab. Majene . Determination of the research location was done intentionally in Kab. Majene because that the area is contain a group of women who process the coconut into oil in small or household scale that still continue to produce until now. The data collection was carried out on August 2018. Results showed that farming business of coconut oil of East Lombong village, Kec. Malunda, Kab. Majene shows that the business is feasible to be run with R/C ratio of 1,15. The guidance is needed to form an institution or group of coconut oil producers as well as an assistance to be able to develop the business and increase the business profits. keywords: Coconut, coconut oil , farm business analysis.